2014
DOI: 10.1186/1471-2458-14-1192
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of vaccination coverage and adherence to the Greek national immunization program among infants aged 2-24 months at the beginning of the economic crisis (2009-2011)

Abstract: BackgroundChildhood immunization has significantly reduced the incidence of vaccine preventable diseases. Parental mistrust over vaccine safety has been associated with vaccine refusal creating barriers on vaccine coverage. Recently, economic crisis has imposed additional impediment.MethodsStudy aim was to evaluate vaccine coverage among infants 2-24 months old in the Athens metropolitan area at the beginning of the economic crisis (2009-2011).ResultsOverall, 1,667 infants were enrolled (mean age 13 months). L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
35
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 18 publications
10
35
1
Order By: Relevance
“…Rates remained very high for all 4 doses, both for the general population and immigrant children. 13,14,20,21 Coverage with 3 DTP doses by 12 months (95.7%), a key WHO indicator, was similar to the estimated coverage for the European region of WHO in 2013. 22 Delay in completing 4 doses by 24 months, although lower than in 2012, is possibly due to the increased number of vaccines in the second year of life.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…Rates remained very high for all 4 doses, both for the general population and immigrant children. 13,14,20,21 Coverage with 3 DTP doses by 12 months (95.7%), a key WHO indicator, was similar to the estimated coverage for the European region of WHO in 2013. 22 Delay in completing 4 doses by 24 months, although lower than in 2012, is possibly due to the increased number of vaccines in the second year of life.…”
Section: Discussionsupporting
confidence: 54%
“…1A), in concordance with local data and suboptimal coverage rates in other countries. 13,14,20,21,28,29 The delay is attributable to the overcrowded vaccination schedule in the first 6 months as well as the nonuniversal use of hexavalent vaccines. The use of combined vaccines has potential benefits, including reduced number of patient visits, fewer complications associated with multiple injections, decreased stocking and visit costs, and lowering the risk of delayed or missed vaccinations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Vaccine coverage studies in children 1-3 y old, have indicated that although hepatitis A vaccine is well accepted by both pediatricians and parents, it is often administered just before entering kindergarten rather then at 12 months of age as recommended by our National Immunization Program. 16,17 This is possibly due to the overcrowded vaccination schedule during the first 24 months of life.…”
Section: Discussionmentioning
confidence: 99%